The meternity to prisioners women and the vertical transmission of DST/AIDS - Giordani, Annecy T.; Bueno, Sônia M.V. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Basis: when thc woman is arrested. she is condemned 10 a sudden ruplure of the maternal affective link. Convicts who are pregnant or still feeding their babies. tose their right lo malemity, sexuality and health. Goals: raise lhe prisoner's perception aboul matemity and children, her needs as mothers separated from lheir children and the affective cffccts rela1cd 10 this question: to guide about lhe vulnerability to STD/AIDS and the HIV vertical transmission. encouraging them 10 become muhiplying agents. Methods: we worked with 14 prisoners in a prison in Sao Paulo's interior, most 18 to 34 ycars old, ali mothers, two aclive homosexuals, most arrested because oftraffic. We developed reasearch-aclion humanist, participalive and quali1a1ive, taped in cassele properly autorized by lhe women wilh posterior transcription, analysis and interprelalion of the tines. Results: matemity, 10 ali of them, has a strong sense of prolection and affect for the children, continuity of lhe species and favorable living experiencc to personal achievements. Toe break wilh the children because of prison causes sorrow, grief, sadness, anguish. loneliness, loss and regret. Conclusions: lhe Penal Law has masculine perspectives and the state do not offer inslilucional structure in favor to the link mother-childrcn. There is discriminatory protecionism in feminine sexuality. which was observed by the difficult access 10 an intimale visil and the health assistance in ali leveis, especially in prevention, are precarious or do not even exist.